Mobile Apps Showcase and Idea Pitching for Grill or Chill at MaGIC Sarawak by Design Technology Program Students - Noorhaslina, Binti Senin; Salmiah, Binti Abdul Hamid (2018)
A Mobile Apps showcase and pitch session was organized on the 8th January by the coordinator course of GKR3014 Interactive Multimedia which involved 112 third year students enrolled for the course from Design Technology Program. There are 36 groups participated for the showcase and 16 groups have been selected from their final assessment to pitch their mobile apps idea for MaGIC Grill or Chill. The Grillers for the GoC session is Syafie Mustafa, Ecosystem Research Analyst, MaGIC and Amirin Arsyan, Procurement Manager, Sarawak Media Group (SMG).